Financial ratio on market capitalization with eps as a moderating variable - Dona Putri Aprillia (Jurnal Mantik, 2024)
This study investigates the effect of financial ratios on market capitalization. This study aims to determine the effect of the Capital Adequacy ratio, Return On Equity, and Non-Performing Loan on market capitalization with EPS as a moderating variable. Study on banking companies listed on the Indonesia Stock Exchange in 2018-2022. This study uses descriptive analysis and multiple regression methods for data analysis. Sampling in this study used a purposive sampling technique with a total of 39 banks. The results of the study answer the main hypothesis that EPS moderates the effect of CAR, ROE, and NPL on market capitalization. The CAR variable has a significant positive effect on market capitalization, while the ROE and NPL variables do not affect market capitalization